A Model for Determining the Strategies and Methods of Developing Iran's Transit and Customs Cooperation with Other Countries - Behzad Jafari; Fereydoun Omidi; Ghasem Rekabdar (پژوهش‌های برنامه و توسعه)
The purpose of this applied research is to present a model for determining the strategies and methods of developing Iran's transit and customs cooperation with other countries. Based on the purpose and nature of this research, a mixed research method was conducted by interviewing research experts; accordingly, the qualitative aspect of the research is based on a grounded theory approach. The statistical population and its data collection method in qualitative and quantitative sections include semi-structured interviews for 12 experts and closed questionnaires for 127 experts and customs managers respectively. Cronbach's alpha was used to test the reliability of the quantitative part of the questionnaire. The data analysis method included a t-test and structural equations, which were analyzed by SPSS and Smart PLS software. According to the findings, the t-statistics calculated is at the level of 0.001. The main categories of the strategic model of transportation, customs, and transit cooperation with other countries include internal organizational factors, knowledge and technology features, international standards, communication, management, gaining experience and training, innovation, strategies, and legislation and policy.